2021
DOI: 10.4153/s0008414x21000316
|View full text |Cite
|
Sign up to set email alerts
|

Tree densities in sparse graph classes

Abstract: What is the maximum number of copies of a fixed forest in an -vertex graph in a graph class G as → ∞? We answer this question for a variety of sparse graph classes G. In particular, we show that the answer is Θ( ( ) ) where ( ) is the size of the largest stable set in the subforest of induced by the vertices of degree at most , for some integer that depends on G. For example, when G is the class of -degenerate graphs then = ; when G is the class of graphs containing no , -minor ( ) then = − 1; and when G is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…It is well‐known that f(n,P2)=3n6 $f(n,{P}_{2})=3n-6$, and it follows from Theorem 3 that f(n,P3)=n2+3n16 $f(n,{P}_{3})={n}^{2}+3n-16$ for n4 $n\ge 4$. The order of magnitude of f(n,H) $f(n,H)$ when H $H$ is a fixed tree was determined in [14] and for general H $H$ (and in arbitrary surfaces) by Huynh et al [22] (see also [21] for results in general sparse settings). In particular, for a path on k $k$ vertices, we have f(n,Pk)=Θ(nk12+1) $f(n,{P}_{k})={\rm{\Theta }}({n}^{\lfloor \frac{k-1}{2}\rfloor +1})$.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…It is well‐known that f(n,P2)=3n6 $f(n,{P}_{2})=3n-6$, and it follows from Theorem 3 that f(n,P3)=n2+3n16 $f(n,{P}_{3})={n}^{2}+3n-16$ for n4 $n\ge 4$. The order of magnitude of f(n,H) $f(n,H)$ when H $H$ is a fixed tree was determined in [14] and for general H $H$ (and in arbitrary surfaces) by Huynh et al [22] (see also [21] for results in general sparse settings). In particular, for a path on k $k$ vertices, we have f(n,Pk)=Θ(nk12+1) $f(n,{P}_{k})={\rm{\Theta }}({n}^{\lfloor \frac{k-1}{2}\rfloor +1})$.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Huynh and Wood [50] introduced the following variant of shortcut systems. A set P of paths in a graph G is a (k, d) * -shortcut system if:…”
Section: Shortcut Systemmentioning
confidence: 99%
“…Huynh and Wood [50] introduced the following generalisation of low-degree squares of graphs: for a graph G and integer d 1, let G (d) be the graph obtained from G by adding a clique on N G (v) for each vertex v ∈ V (G) with deg G (v) d. Huynh and Wood [50] observed that G (d) = G P where P is some (2, d) ⋆ -shortcut system.…”
Section: Powers Of Planar Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this result, Alon and Caro [1] determined N n K ( , ) m 2,  exactly for all m, where K m 2, is the complete 2-by-m bipartite graph. In a series of works [3,8,11,16], which culminated with a recent paper of Huynh, Joret and Wood [10], the asymptotic value of N n H ( , )…”
mentioning
confidence: 99%